Childhood trauma- and cannabis-associated microstructural white matter changes in patients with psychotic disorder: a longitudinal family-based diffusion imaging study. Issue 4 (29th May 2018) - Domen, Patrick; Michielse, Stijn; Peeters, Sanne; Viechtbauer, Wolfgang; van Os, Jim; Marcelis, Machteld; ,
Abstract: Background: Decreased white matter (WM) integrity in patients with psychotic disorder has been a consistent finding in diffusion tensor imaging (DTI) studies. However, the contribution of environmental risk factors to these WM alterations is rarely investigated. The current study examines whether individuals with (increased risk for) psychotic disorder will show increased WM integrity change over time with increasing levels of childhood trauma and cannabis exposure. Methods: DTI scans were obtained from 85 patients with a psychotic disorder, 93 non-psychotic siblings and 80 healthy controls, of which 60% were rescanned 3 years later. In a whole-brain voxel-based analysis, associations between change in fractional anisotropy (ΔFA) and environmental exposures as well as interactions between group and environmental exposure in the model of FA and ΔFA were investigated. Analyses were adjusted for a priori hypothesized confounding variables: age, sex, and level of education. Results: At baseline, no significant associations were found between FA and both environmental risk factors. At follow-up as well as over a 3-year interval, significant interactions between group and, respectively, cannabis exposure and childhood trauma exposure in the model of FA and ΔFA were found. Patients showed more FA decrease over time compared with both controls and siblings when exposed to higher levels of cannabis or childhood trauma. Conclusions: Higher levels of cannabis or childhood trauma may compromise connectivity over the course of the illness in patients, but not in individuals at low or higher than average genetic risk for psychotic disorder, suggesting interactions between the environment and illness-related factors.